Expo 85 : 85 jaar Belgische kunst. - Van de Velde, Ronny; Peeters, Fabienne (s.l. : Delen Private Bank, 2021)
De Cock, Jan ; Callewaert Vanlangendonck Gallery ; Saverys, Jan ; Bury, Pol ; Plomteux, Léopold ; Boel, Maurice ; Peire, Luc ; Van Hoeydonck, Paul ; Vandenbranden, Guy ; Cox, Jan ; Vandercam, Serge ; Overberghe, Cel ; Leblanc, Walter ; Dries, Jan ; Decock, Gilbert ; Verstockt, Mark ; Verdren, Marcel-Henri ; Van den Abbeel, Jan ; Bogart, Bram ; Swimberghe, Gilbert ; Noël, Victor ; Meyer, Jef ; Gallery Sofie Van de Velde ; Mees, Guy ; D'Hollander, Ilse ; Maes, Ives ; Van den Broek, Koen ; Tyberghein, Charline ; Hanssen, Karin ; Jennes, Pieter ; Eyckermans, Bendt ; De Boe, Rik ; Driesen, Stef ; Gilliams, Gommaar ; Roberts, Perry ; De Sauter, Willy ; Borghouts, Karin ; Plus-One Gallery ; Aerts, Nel ; De Beukelaer, Sergio ; Gerhard, Tatjana ; Gobyn, Ritsart ; Grunewald, Manor ; Vanderlinden, Carole ; Vervaet, Filip
Expo 85, Delen Private Bank, Antwerpen, 2021
boek